2015
DOI: 10.1111/all.12645
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to galacto‐oligosaccharides – an evaluation in an atopic population in Singapore

Abstract: Anaphylaxis to galacto-oligosaccharides (GOS), a prebiotic, has been described in atopic patients following its supplementation in commercial milk formula in South-East Asia. The epidemiology of this usual allergy to a carbohydrate is unknown. This study evaluated the prevalence of allergy to two formulations of commercial GOS, Vivinal™ GOS (vGOS) and Oligomate™ , in an atopic cohort. Atopic subjects (n = 487) from two specialist allergy clinics were surveyed via structured questionnaire and underwent skin pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Further investigation proved that the trigger was galacto-oligosaccharide, a prebiotic added to cow's milk formula [36]. Since 2009, we have identified 25 confirmed cases among schoolchildren and adults, 16 of whom have been described in previous publications [36][37][38]. These subjects reacted to galacto-oligosaccharide-supplemented formula milk with the predominant symptoms of dyspnoea, wheeze, angioedema, and urticaria.…”
Section: Discussionmentioning
confidence: 85%
“…Further investigation proved that the trigger was galacto-oligosaccharide, a prebiotic added to cow's milk formula [36]. Since 2009, we have identified 25 confirmed cases among schoolchildren and adults, 16 of whom have been described in previous publications [36][37][38]. These subjects reacted to galacto-oligosaccharide-supplemented formula milk with the predominant symptoms of dyspnoea, wheeze, angioedema, and urticaria.…”
Section: Discussionmentioning
confidence: 85%
“…demonstrated that these patients were sensitized to short chain (sc) GOS rather than to cow's milk or long-chain fructo-oligosaccharides 116 . These reactions occur more commonly in atopic individuals, and GOS allergy was estimated to occur in about 3.6% of the atopic Singaporean population 118 . The primary sensitizer for GOS allergy in South East Asia currently remains unknown, but it is postulated to be a trigger that is specific to Asia.…”
Section: Food Allergensmentioning
confidence: 99%
“…Chiang et al demonstrated that all five patients were sensitized to short‐chain (sc) GOS and fractions of scGOS containing 3 sugar units or greater but not to cow's milk or long‐chain fructo‐oligosaccharides. The prevalence of GOS allergy has now been estimated to be around 3.6% in the atopic Singaporean population . In contrast to α‐Gal/red meat allergy, the primary sensitizer for GOS allergy remains unknown, but postulated to be a substance geographically restricted to Asia.…”
Section: Anaphylaxis Triggers—east Vs Westmentioning
confidence: 99%
“…The prevalence of GOS allergy has now been estimated to be around 3.6% in the atopic Singaporean population. 48 In contrast to α-Gal/red meat allergy, the primary sensitizer for GOS allergy remains unknown, but postulated to be a substance geographically restricted to Asia.…”
Section: Galacto-oligosaccharide Allergy First Came To Attention Inmentioning
confidence: 99%